Las ideas no tienen historia - Valenzuela, Fernando (Revista Chilena de Humanidades, 2015)
Professor Valenzuela looks into Ortega’s thesis of the inexistence of a hi story ofideas, which the Spanish thinker elaborates from his principie of man and his circumstance. For this purpose Prof. Valenzuela formulates critica! comments which he derives from Husserl’s Prologue to bis Logical Investigations, and which he applies to Ortega’s wo rk, History as System. The author then discusses the relationship th at has been established between Ortega’s doctrine of ideas and the pragmatic paradigm, in order to distinguish between idea and belief in Ortega’s system. At the same time he emphasizes the interest which Ortega awoke in Hispanic America, which contributed to a deper knowledge of German thought, while giving a Spanish form to the European logos without betraying the sense of an American authenticity.